1993
DOI: 10.1111/j.1365-2621.1993.tb04308.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt, Phosphate and Oil Temperature Effects on Emulsion Capacity of Fresh or Frozen Meat and Sheep Tail Fat

Abstract: The effects of K2HP0,,, NaCl and oil temperature on emulsion capacity (EC) and microstructure of fresh and frozen Turkish beef was studied by utilizing a model system. EC of frozen meat was 6.4% higher than fresh meat. EC also increased with increasing phosphate levels increasing 8.5 and 10.4% over the control with 0.50 and 0.75% phosphate respectively. EC increased 1.6% for 3.0% salt over 2.5% salt. Microstructure photographs of the phosphate containing emulsions indicated the protein aggregates diminished an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Shand (2000) reported that an increase in emulsion viscosity is related to an increase in emulsion stability. Also, Zorba et al (1993) and Zayas (1997) showed that emulsion systems had higher correlations between emulsion viscosity and emulsion stability. These results are in agreement with those of Aktas and Genccelep (2006), who found that frankfurters with added high-dietary fiber increased the viscosity of meat batter, and the report of Saricoban et al (2008) that an increase in fat content while maintaining constant dietary fiber levels led to an increase in viscosity.…”
Section: A -Cmentioning
confidence: 99%
“…Shand (2000) reported that an increase in emulsion viscosity is related to an increase in emulsion stability. Also, Zorba et al (1993) and Zayas (1997) showed that emulsion systems had higher correlations between emulsion viscosity and emulsion stability. These results are in agreement with those of Aktas and Genccelep (2006), who found that frankfurters with added high-dietary fiber increased the viscosity of meat batter, and the report of Saricoban et al (2008) that an increase in fat content while maintaining constant dietary fiber levels led to an increase in viscosity.…”
Section: A -Cmentioning
confidence: 99%
“…Lee et al (2008) indicated that dietary fiber provides higher water retention and improved viscosity. Some studies have reported that the viscosity of emulsion batter is important related to emulsion stability (Shand, 2000;Zayas, 1997;Zorba et al, 1993). Aktas and Genccelep (2006) indicated that emulsion sausage batters had a higher correlation with added high-dietary fiber and increased the viscosity of meat batters.…”
mentioning
confidence: 99%
“…When pH moves furthers away from the isoelectric point of the muscle proteins, the net electric charge increases. It can cause an increase in solubility and water holding capacity of proteins (Zorba et al, 1993a(Zorba et al, , 1993b. The decreasing in protein content may be related to an increase in protein solubility and relative moisture content.…”
Section: Discussionmentioning
confidence: 98%